Vocational education and training in the age of digitization challenges and opportunities - Wuttke, Eveline 1960-; Seifried, Jürgen 1967-; Niegemann, Helmut M. 1947- (Verlag Barbara Budrich, 2020)
The increasing digitization of the world of work is associated with accelerated structural changes. These are connected with changed qualification profiles and thus new challenges for vocational education and training (VET). Companies, vocational schools and other educational institutions must respond appropriately. The volume focuses on the diverse demands placed on teachers, learners and educational institutions in vocational education and training and aims to provide up-to-date results on learning in the digital age. Mit der zunehmenden Digitalisierung der Arbeitswelt ist ein beschleunigter Strukturwandel verbunden, der veränderte Qualifikationsprofile und damit neue Herausforderungen für die berufliche Aus- und Weiterbildung mit sich bringt. Betriebe, berufliche Schulen und andere Bildungsinstitutionen müssen darauf in angemessener Weise reagieren. Der Band nimmt die vielfältigen Anforderungen an Lehrende, Lernende und Bildungsinstitutionen der beruflichen Aus- und Weiterbildung in den Blick und stellt aktuelle Ergebnisse zum Lernen im digitalen Zeitalter zur Verfügung
Keywords: Unterrichtstechnologie; Digitalisierung; Betriebliche Ausbildung; Mediendidaktik; Arbeitswelt; berufliche Bildung und Ausbildung; digital media; digitale Medien; digitalization; instructional technology; learning in the digital age; Lernen im digitalen Zeitalter; vocational education and training; world of work; Aufsatzsammlung